The Risk of Breast Cancer in Women with a BRCA1 Mutation from North America and Poland - Lubinski, Jan (2011)
Women with a BRCA1 mutation face a high lifetime risk of breast cancer. It is unknown to what extent environmental factors modify the inherent genetic risk. If women from different countries, but with similar mutations, experience different levels of cancer risk, non-genetic risk modifiers are likely to be present. Study subjects were a cohort of 1477 women with a BRCA1 mutation, from Canada (n = 358), the United States (n = 256) and Poland (n = 863). The women were followed for a mean of 4.3 years and 130 incident cases of breast cancer were recorded. Annual cancer incidence rates were calculated, and based on these, penetrance curves were constructed for women from North America and Poland. In a Cox proportional hazards model, residence in Poland, versus North America, was associated with an adjusted hazard ratio of 0.54 (95% CI 0.34-0.86; p = 0.01). The risk of breast cancer to age 70 was estimated to be 49% for women from Poland and 72% for women from North America. Among women with BRCA1 mutations, the risk of breast cancer in women who reside in Poland is less than that of women who reside in North America. The reasons for the difference are unknown, but this observation suggests that environmental factors or genetic modifiers are important in determining risk.